(untitled) (KULT_online, 2018)
Nelly van Doorn-Harder’s edited volume Copts in Context Negotiating Identity, Tradition, and Modernity utilizes various analytical tools to investigate Coptic Christianity. The authors of this multi-disciplinary volume show how identity, traditions, and diaspora are three ways through which the political, theological, and socioeconomic history and everydayness of the largest minority in the Middle East can be negotiated. To make sense of the complexities entangled with these three dimensions, the book mainly studies the attempts of Coptic Christians to solve the challenges that stand against the ‘visibility’ and the ‘stability’ of their faith. The book adequately emphasizes the ambiguity of the unfixed boundaries that define the meaning of and the belonging to an imagined Coptic community.